Model Penilaian Pembelajaran Daring Saat Pandemi di RA Perwanida Surabaya - Ilun Mualifah; Silatur Rohma; Miftakhul Jannah; Zayyana Zahrotul Fitri (Program Studi Pendidikan Islam Anak Usia Dini, UIN Sunan Ampel Surabaya, 2021)
The purpose of this study was to describe and analyze the learning assessment model applied in the RA Perwanida Ketintang Surabaya institution during online learning. This research uses a qualitative approach with the type of case study research. The data collection techniques used were participatory observation, interviews, and documentation. The data analysis technique used the interactive model of Miles and Huberman's analysis, and the data validity was tested using the triangulation method. The results of the study found that RA Perwanida Surabaya used a goal-oriented assessment model and a conformity assessment model. The conclusion of this research shows that in RA Perwanida Surabaya, the assessment is carried out using the following assessment instruments: anecdotal notes, work results and checklists. The assessment is carried out with a goal-oriented model and a suitability model.